Globally Exponential Stability of Periodic Solutions to Impulsive Neural Networks with Time-Varying Delays - Yuanfu Shao; Changjin Xu; Qianhong Zhang (Abstract and Applied Analysis)
By using Schaeffer's theorem and Lyapunov functional, sufficient conditions of the existence and globally exponential stability of positive periodic solution to an impulsive neural network with time-varying delays are established. Applications, examples, and numerical analysis are given to illustrate the effectiveness of the main results.